Production of Liquid Compost with EM4 Bio Activator Volume Variation from Vegetable and Fruit Waste - Nasution, Nanda Eska Anugrah; Rizka, Chairany Rizka (Aspirasi Masyarakat Intelektual Islam Nusantara, 2022)
Compost is a combination of substances used to enrich and nourish the soil. Compost availability is highly beneficial to agriculture. Using EM4 Bio Activator, vegetable and fruit waste may be converted into compost instead of being thrown. The objective of this study is to determine the best amount of EM4 Bio Activator for creating liquid compost. This research uses vegetable and fruit waste, such as pineapple, spinach, banana, long beans, banana stem, papaya, and coconut water, along with a small amount of sugar, as the fermentation's primary ingredient. Variations in the treatment volume of EM4 Bio Activator were 5 mL, 10 mL, and 15 mL. The fermentation process lasts one week. The results conclude that the addition of 10 mL of EM4 Bio Activator is optimal for fermenting Vegetable and Fruit Waste (with the amount specified in the study technique) into Liquid Compost or perhaps EM4 Bio Activator. The approximate ratio for one week of fermentation is 10 mL EM4 Bio Activator per 1.7 kg of mixed ingredients.